Prevalence of Work-Related Musculoskeletal Problems and Perceived Job Risk Factors among Nurses at Tertiary Level Hospitals in Sylhet (Jalalabad Medical Journal, 2026)
Work-Related Musculoskeletal Problems (WRMSPs) present a significant health concern, particularly among nurses in tertiary-level hospitals. This cross-sectional study, conducted from January 1 to December 31, 2019, investigated the prevalence of WRMSPs and the perceived job risk factors of WRMSPs among 307 nurses from Jalalabad Ragib-Rabeya Medical College Hospital and Sylhet Women's Medical College Hospital in Sylhet district, Bangladesh. By employing a previously validated semi-structured four-sectioned questionnaire, data on socio-demographics, work-related factors, perceived job risks, and the Nordic Musculoskeletal Questionnaire (NMQ) for musculoskeletal pain were collected and analysed using SPSS version 25. The results revealed that 66.1% of the participants had WRMSPs in the past 12 months. A significant correlation between MSP and age was identified (p-value=0.002). The findings reveal a higher prevalence of musculoskeletal disorders among females. Treating an excessive number of patients in one day (99%), bending or twisting the back in an awkward posture (90.2%), and working very fast for short periods (lifting, grasping, pulling, etc.) (91.9%) were the most perceived job risk factors. Statistically significant associations were found between WRMSPs and various occupational factors, including managing patients with disabilities (p=0.012), treating an excessive number of patients (p=0.038), awkward back movements (p=0.018), and lifting heavy materials (p=0.009). Given the high prevalence of work-related musculoskeletal disorders among nurses in this study and the strong association with specific risk factors, these findings emphasise the need for structured ergonomic programs and improved work conditions to mitigate WRMSPs and enhance nurses' productivity and job satisfaction.Jalalabad Med J 2025; 22 (2): 55-60.